Project-based learning based on local wisdom through google classroom to improve process skills in pandemic times - Maria Waldetrudis Lidi; Maimunah H Daud (Universitas Ahmad Dahlan, 2021)
This research aims to improve the science process skills of biology education students during the Covid 19 pandemic. This research was carried out at the Biology Education Study Program, the University of Flores, from May to July 2021. The type of research used is experimental research with observation and product assessment. The process skills, performance, and product assessment data are then analyzed using a simple statistical formula and then converted into value categories and interpreted based on the criteria. The quality of improving science process skills is measured using the N-gain formula and categorized based on the rubric of improvement interpretation. The results show that project-based learning based on local wisdom through google classroom is proven to train science process skills 85% to 89% in the good category with the quality test for improving science process skills in the high category. In addition, the results of measuring project performance skills that integrate the potential of local wisdom in the project get a score of 85% to 90% in the good and very good categories. Product ratings get an average score of 87% for product appearance and 83% for product quality, and both are in a good category. So, it can be concluded that the project-based learning (PjBl) model based on local wisdom through the google classroom media can train and improve several science process skills and performance can also increase the competence of prospective biology teacher students through real work of scientific product creativity.